The Comprehensive Qur’anic Perspective on Women’s Rights: A Comparative Study of Surah al-Nisa and Surah al-Nur - Dr. Syed Iftikhar Ahmad; Hammad Sultan Ul Qadri; Sagheer Hussain (Journal of Religion and Society, 2025)
This research article presents a comparative analysis of women’s rights as outlined in Surah al-Nisa and Surah al-Nur, examined through the interpretations of Tafsir Tibyan al-Qur’an and Tafsir Sirat al-Jinan. Surah al-Nisa addresses key issues such as financial support, inheritance, marriage, dowry, and marital responsibilities, while Surah al-Nur emphasizes chastity, protection against false accusations, and the guidelines for modesty. The study highlights how Tafsir Tibyan al-Qur’an elaborates on these rights with in-depth scholarly reasoning rooted in Hadith and Fiqh, whereas Tafsir Sirat al-Jinan presents them in a simplified and accessible manner for the general reader. The comparative approach demonstrates that the Qur’anic concept of women’s rights is comprehensive, balanced, and practical upholding women’s dignity while fostering justice and social harmony. This paper underscores the importance of combining scholarly depth with public accessibility to ensure the effective transmission of Qur’anic teachings in society. Keywords: Qur’an, Women’s Rights, Surah al-Nisa, Surah al-Nur, Tafsir Tibyan al-Qur’an, Tafsir Sirat al-Jinan, Comparative Study, Islamic Law, Gender Justice